Mapping the Future: A Content Analysis of the Evolution of Gene Therapy in Urological Cancer - Muhammad Sidharta Krisna; Muhammad Alfi Reza; Bobby Aksanda Putra; Bukhari Muslim Siregar; Muhammad Alif Adhani (CV. Inara, 2025)
Background: Gene Therapy Has Emerged As A Promising Approach In The Treatment Of Urological Cancers, Including Prostate, Kidney, And Bladder Cancers. Over The Past Decade, Significant Advancements Have Been Made In Gene Editing Technologies Such As Crispr-Cas9, Rna-Based Therapies, And Viral Vector Systems. These Innovations Offer Precise Targeting Of Oncogenes And Tumor Suppressor Genes, Potentially Improving Treatment Efficacy And Reducing Adverse Effects Compared To Conventional Therapies. Methods: A Systematic Content Analysis Was Conducted On Peer-Reviewed Literature And Clinical Trial Reports From 2015 To 2025. Databases Such As Pubmed, Sciencedirect, And Scopus Were Used To Extract Relevant Studies. Inclusion Criteria Encompassed Original Research Articles, Systematic Reviews, And Clinical Trials Focused On Gene Therapy Applications In Prostate, Kidney, And Bladder Cancer. Studies Exclusively Conducted On In Vitro Or Animal Models Without Clinical Relevance Were Excluded. Results: Crispr-Cas9 Has Demonstrated High Precision In Gene Editing, Particularly In Prostate Cancer, Where Targeting Androgen Receptor-Related Genes Has Enhanced Hormone Therapy Sensitivity. Rna Therapy, Especially Using Sirna Targeting Vegf And Hif-1α, Has Shown Promise In Kidney Cancer Treatment By Inhibiting Angiogenesis. Viral Vectors Remain A Primary Method For Gene Delivery In Bladder Cancer, Although Immune Responses Pose A Significant Challenge. Clinical Trials Indicate That Gene Therapy Combined With Immunotherapy, Particularly Checkpoint Inhibitors Like Pembrolizumab, Enhances Treatment Efficacy. However, Regulatory Barriers, High Costs (Estimated At Over 500,000 Per Patient), And Safety Concerns Regarding Off-Target Effects Remain Major Obstacles To Widespread Clinical Implementation. Conclusion: Despite These Challenges, Gene Therapy Holds Great Potential For Revolutionizing Urological Cancer Treatment. Future Research Should Focus On Optimizing Gene Delivery Systems, Reducing Off-Target Risks, And Developing Cost-Effective Production Methods. Personalized Gene Therapy Approaches, Leveraging Advancements In Genomic Sequencing, Are Expected To Further Enhance Treatment Precision. With Continued Innovation And Regulatory Advancements, Gene Therapy Is Anticipated To Become An Integral Part Of Standard Urological Cancer Care In The Coming Decade.